Statistical methods for analysing the spatial dimension of changes in land use and farming systems - Lesschen, Jan Peter; Verburg, P.H.; Staal, Steven J. (International Livestock Research Institute, 2005)
This Report provides an overview of empirical methods that are frequently used for the analysis of spatial patterns of LUCC based on a survey of recent literature. Because these methods are relevant for wider analysis of system change beyond LUCC (Land Use and Land Cover Change), some examples of analysis of livestock systems are included. The descriptions are not detailed, with the emphasis being instead on explaining the concepts in simple terms, with the aid of illustrations of these methods in land use research. The references refer to detailed descriptions, applications or textbooks. The methods discussed in this Report aim at uses of different types of spatially differentiated data at different scales, including both household-and pixel-level analysis. Furthermore, a number of issues important to spatial analysis of land use and farming system change are discussed, including data representation, spatial autocorrelation and validation issues. This information is believed to facilitate the application of these methods in LUCC and other studies and provide an overview of the possibilities and limitations of empirical methods to unravel the complexity of spatial variation in land use and farming system change.